Alternative Studies Abutment Structure and Bridge Oprit on Soft Soil at Belanti Food Estate Area, Pulang Pisau Regency, Central Kalimantan (Case Study : Muara Tahai Bridge Sta. 0+100) - Mariadi, Asrul; Endah Mochtar, Noor; Marbun, Riwanto (Journal of Infrastructure & Facility Asset Management, 2025)
One of the PSN progarm is the improvement of Muara Tahai Bridge that located in Pulang Pisau Regency. The existing design of the substructures uses steel piles with a diameter of 50 cm and a depth of 28 meters due to soft soil condition. After a few trial, the effective design using piles can be done with the depth 20 meter with Pmax control of 34.65 tons < P allowed for group piles of 41.81 tons. An alternative design as a substructure is using floating foundation, which is concrete foundation using floaton material in it. The floating foundation dimension is 10 meter long, 3.2 meter width and 1,5 meter thick. The bearing capacity of the floating foundation using Terzaghi theory is 5,02 Ton/m2.